OPTIMALISASI PEMBERDAYAAN KARANG TARUNA DALAM PENGEMBANGAN DESA SILOMUKTI KABUPATEN SITUBONDO - Luckman Ashary (UPT Penerbitan Universitas Jember)
This study aims to determine the extent of the optimization potential of the Youth affect the development of the village Silomukti in Situbondo. Analysis of the data in this study through the work process analysis consists of three flow of activities, such activities are data reduction, data presentation, and drawing conclusions. Youth has a strategic role in the development of social welfare because of the presence of Youth which was nearly all the villages / wards in direct contact with social welfare issues as well as potential and other social welfare resources. The government realized that without public participation impossible social problems can be dealt with, for it is expected the participation of all potential and social welfare resources including Youth. But behind its potential, the role of today's youth tend to be barren. Lack of sufficient productive activities that make the existence of the existence of the Youth to be just another big name youth organizations. Weak institutional board of the Youth in optimizing the potential of its members into the most prominent problems in Karang Taruna. This is compounded by the lack of bargaining power that seemed promising at this youth organization, so that the younger generation can not see the importance of the existence of this organization.